2020
DOI: 10.3390/brainsci10100748
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and Somatosensory P3 Are Complementary for the Assessment of Patients with Disorders of Consciousness

Abstract: The evaluation of the level of consciousness in patients with disorders of consciousness (DOC) is primarily based on behavioural assessments. Patients with unresponsive wakefulness syndrome (UWS) do not show any sign of awareness of their environment, while minimally conscious state (MCS) patients show reproducible but fluctuating signs of awareness. Some patients, although with remaining cognitive abilities, are not able to exhibit overt voluntary responses at the bedside and may be misdiagnosed as UWS. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
(57 reference statements)
0
17
0
Order By: Relevance
“…They did not find differences in the P300 characteristics when comparing UWS to MCS patients or even when comparing traumatic vs. non-traumatic etiologies. The performances of the two different stimuli (auditory and vibrotactile) were independent of each other [120]. Investigating the P300 response in relation to the CRS-R score, it was shown that the amplitude of the novelty P300 is correlated with the CRS-R and even more with the auditory sub-score [105].…”
Section: P300mentioning
confidence: 98%
“…They did not find differences in the P300 characteristics when comparing UWS to MCS patients or even when comparing traumatic vs. non-traumatic etiologies. The performances of the two different stimuli (auditory and vibrotactile) were independent of each other [120]. Investigating the P300 response in relation to the CRS-R score, it was shown that the amplitude of the novelty P300 is correlated with the CRS-R and even more with the auditory sub-score [105].…”
Section: P300mentioning
confidence: 98%
“…Surprisingly, only around one-fifth of EVE-BCI studies were carried out for patients. These patients suffered from multiple levels of motor functioning loses caused by different diseases including the unresponsive wakefulness syndrome (UWS) [ 8 , 79 ], disorder of consciousness (DOC) [ 9 , 49 , 61 , 63 , 70 ], amyotrophic lateral sclerosis (ALS) [ 54 , 57 , 87 , 89 , 103 ], locked-in syndrome (LIS) [ 58 , 63 , 70 , 78 ], stroke [ 94 ], and minimally conscious state (MCS) [ 86 ]. On the other hand, most studies (83.54% of cases) alternatively focused on healthy subjects covering adults of all ages, including young people, the middle-aged, and elders.…”
Section: Resultsmentioning
confidence: 99%
“…Studies involving the above 20 participants contributed 7.59% of cases. The largest sample size among selected papers was 52, with forty DOC patients and twelve healthy people [ 49 ]. Only a tiny proportion represented the finding of a case study involving a single subject only, accounting for 5.06% of cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Annen et al ( 2020) proposed a P300based paradigm with auditory and vibrotactile stimulation which was supposed to evoke auditory-evoked potentials (AEP) and vibrotactile-evoked somatosensory potentials (VTP). 34 Forty patients with DoC and 12 healthy participants were separated into four groups (healthy participants, patients in an EMCS, patients in an MCS, and patients in a VS/UWS). The relationships between groups and 'differentiated response' in none, either or both paradigms were investigated, and a logarithmic regression model was then used to analyze the recorded P300 response data.…”
Section: Accepted Manuscriptmentioning
confidence: 99%